To Determine the Frequency of Thrombocytopenia in Neonatal Sepsis - Ghulam Hussain, Furqan Ahmad, Sohail Akhtar, Sara Khan, Faiza, Zulqarnain Haider (Pakistan Journal of Medical & Health Sciences, 2023)
Background: During the first month of life, a baby may develop neonatal sepsis, a clinical state of bacterial infection marked by signs and symptoms of systemic involvement. There is a high mortality and morbidity rate linked with neonatal sepsis. Objective: The goal of this study is to quantify the incidence of thrombocytopenia among babies with sepsis who come to the Hayatabad Medical Complex in Peshawar. Methods: This cross-sectional study after the ethical approval the study was conducted at the Pediatrics Department of Hayatabad Medical Complex, Peshawar from 17-03-2020 to 17-09-2020. A total of 112 neonates up to 28 days of age with neonatal sepsis were included in the study in a consecutive manner and checked for platelet count to detect thrombocytopenia. Results: The mean age of the sample was 14.2 ± 6.8 days. Out of 112 neonates included in the study, there were 66.1% male patients and 33.9% female patients. Mean gestational age at birth was 39.4 ± 1.7 weeks. Mean birth weight of the neonate according to records was 3.1 ± 0.8 kg. 46% of the neonates have the Thrombocytopenia. No significant difference in the age (P=0.445), gender of neonate (P=0.085), gestational age at birth (P= 0.356), weight at birth wise (P= 0.456) stratification of the Thrombocytopenia was observed in the study participants. Practical implication: this study will help to determine the frequency of neonatal sepsis in Pakistani general population and will also highlight the factor associated with increased chance of neonatal sepsis in thrombocytopenia. Conclusion: Neonates with sepsis often exhibit thrombocytopenia. No firm conclusions can be drawn about the relationship between Thrombocytopenia and sepsis from this research. Keywords: Thrombocytopenia, neonatal sepsis, meningitis, platelet count